Patterns and severity of vincristine‐induced peripheral neuropathy in children with acute lymphoblastic leukemia. Issue 1 (March 2015) - Lavoie Smith, Ellen M.; Li, Lang; Chiang, ChienWei; Thomas, Karin; Hutchinson, Raymond J.; Wells, Elizabeth M.; Ho, Richard H.; Skiles, Jodi; Chakraborty, Arindom; Bridges, Celia M.; Renbarger, Jamie
Abstract Vincristine, a critical component of combination chemotherapy treatment for pediatric acute lymphoblastic leukemia (ALL), can lead to vincristine‐induced peripheral neuropathy (VIPN). Longitudinal VIPN assessments were obtained over 12 months from newly diagnosed children with ALL (N = 128) aged 1–18 years who received vincristine at one of four academic children's hospitals. VIPN assessments were obtained using the Total Neuropathy Score‐Pediatric Vincristine (TNS©‐PV), National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE©), Balis© grading scale, and Pediatric Neuropathic Pain Scale©–Five (PNPS©‐5). Of children who provided a full TNS©‐PV score, 85/109 (78%) developed VIPN (TNS©‐PV ≥4). Mean TNS©‐PV, grading scale, and pain scores were low. CTCAE©‐derived grades 3 and 4 sensory and motor VIPN occurred in 1.6%/0%, and 1.9%/0% of subjects, respectively. VIPN did not resolve in months 8–12 despite decreasing dose density. VIPN was worse in older children. Partition cluster analysis revealed 2–3 patient clusters; one cluster (n = 14) experienced severe VIPN. In this population, VIPN occurs more commonly than previous research suggests, persists throughout the first year of treatment, and can be severe.